INOVASI PELAYANAN PERIZINAN MELALUI ONLINE SINGLE SUBMISSION (OSS) STUDI PADA IZIN USAHA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BEKASI: INOVASI PELAYANAN PERIZINAN MELALUI ONLINE SINGLE SUBMISSION (OSS) (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2019)
Business licenses, especially in the industrial area, are an obligation for every entrepreneur who has assets in the area. So the focus of this research is on the implementation of licensing services trying to be integrated electronically to the acceleration of business licensing in Bekasi Regency in 2018. Based on the identification results obtained by researchers, OSS is a new government policy that utilizes internet technology. Bekasi Regency DPM-PTSP became the government's pilot project in implementing the Online Single Submission (OSS). Then an in-depth study is needed on how the Bekasi Regency DPM-PTSP will carry out the Online Single Submission (OSS). The research method chosen was a descriptive qualitative approach. This study uses the Edward III theory which measures the success variables of policy implementation with 4 things namely communication, resources, disposition, and bureaucratic structure. Based on the results of the study, licensing services are trying to integrate electronically to the acceleration of business licensing in Bekasi Regency, but the efforts are not yet running optimally, obstacles are still often faced by DPM-PTSP, especially about supporting facilities.